Lei Aldir Blanc e Sistema Nacional de Cultura: a implementação da Lei de Emergência Cultural e suas influências no Sistema Municipal de Cultura de João Pessoa/PB (2020-2022) - Moura, Gabriel Borges de Lima e (2023)
Instituted in an adverse political-institutional environment for Brazilian cultural policies, the LAB was the main emergency public policy to support the cultural sector in all states and municipalities of the country during the pandemic. Considering that the municipalities that have more institutionalized culture systems have better adapted to the federative logic of resource decentralization and that, in general, the LAB has generated a positive externality by stimulating the SNC policy and the Municipal Culture Systems (SEMENSATO and BARBALHO, 2021), this research has the general objective of analyzing the implementation of the LAB in João Pessoa/PB (2020-2022) as to its local influences on the SNC public policy and the state capacities activated or not in municipal public management. By means of a case study (method), the methodological path planned for this research articulates the techniques of participant observation, document analysis and interviews, having as methodological reference the approach of institutional arrangements of implementation (PIRES and GOMIDE, 2018, 2021). Finally, we observed that the implementation of the LAB challenged all dimensions of state capacities, provoking the activation of capacities of the municipality of João Pessoa/PB in the political-relational, technical-administrative and cognitive dimensionswithout however having generated structuring activations-, besides having stimulated elements integrating the SMC of the Paraíba capital, especially the CMPC, FUNJOPE and the FMC, in the face of continuous pressure from organized civil society.